A STUDY ON THE EFFECTIVENESS OF USING WEB BASED ENGLISH LEARNING MEDIA FOR NEW-COMING STUDENTS OF POLBENG - Arita Destianingsih; Ari Satria (INOVISH JOURNAL, 2017)
Abstract: The aim of this study was to know the effectiveness of the use of web-based English learning media for new-coming students of State Polytechnic of Bengkalis as interactive media to learn English which was not restricted in the classroom only. This study belongs to the quasi experimental research and presents pre-test, post test and to investigate the effect of using web-based English media in mastering basic English. The participants were new coming students from the first semester (N=54) of State Polytechnic Bengkalis and divided into two groups. Both groups were taught English at basic level, however, the experimental group students who are exposed to web based English media and the controlled group students who received conventional method. Pre-test and post-test were given to both experimental group students and controlled group students. The score of the tests were compared through independent sample t-test. The mean value of pre-test of experimental class was 61.35, while the control class was 52.23. After learning using the website in experimental class the mean value obtained in post-test was 78.85, while in control class was 59.04. The improved of learning outcomes can be seen from the level of significance was 0.000 and it was lower than t test 0.000<0.05. It means that the hypothesis null is not accepted. Therefore, it can be concluded that the score of the students in learning basic English learning material between the experimental group and control group was significantly different. The experimental group students who learned basic English learning material using web-based English learning media had increased their basic English knowledge.